Emphasis in Surah Al-Hashr and its effect in directing the meaning - Allawi, Adel Saleh (Journal of Tikrit University for Humanities, 2024)
Praise be to God, Lord of the Worlds, and may God’s blessings and peace be upon our Prophet Muhammad and his family and descendants. As for what follows: God Almighty has assigned miracles to every prophet, and has singled out our Prophet Muhammad (may God bless him and grant him peace) miracles that will last forever until the Day of Resurrection, the greatest of which is the Holy Qur’an, which dazzled minds with its style and organization, and with which he challenged the worlds of the jinn and humans together to produce something like him, so they were unable to do so, and he singled it out for him. God Almighty made it a miracle without other heavenly books, and He did not describe it in the same way as He described the Qur’an. It came in Al-Itqan: ((The judge said: If it is said: Do you say that there are words other than the Qur’an that are miraculous, like the Torah and the Gospel? We say: None of that is a miracle in verses. And the composition, even if it is miraculous like the Qur’an in what it contains of information about the unseen, it was not miraculous because God did not describe it in the way that the Qur’an described it, and because we know that it was not challenged as it occurred in the Qur’an, and because that language does not contain the aspects of eloquence in which differentiation occurs. Which ends in miraculousness))